Stochastic gravitational background from inflationary phase transitions - Baccigalupi, Carlo; Amendola, Luca (Arxiv, 1997)
We consider true vacuum bubbles generated in a first order phase transition occurring during the slow rolling era of a two field inflation: it is known that gravitational waves are produced by the collision of such bubbles. We find that the epoch of the phase transition strongly affects the characteristic peak frequency of the gravitational waves, causing an observationally interesting redshift in addition to the post-inflationary expansion. In particular it is found that a phase transition occurring typically 10$\div$20